2011
DOI: 10.1007/s11511-012-0069-3
|View full text |Cite
|
Sign up to set email alerts
|

Random conformal weldings

Abstract: We construct a conformally invariant random family of closed curves in the plane by welding of random homeomorphisms of the unit circle. The homeomorphism is constructed using the exponential of βX where X is the restriction of the two dimensional free field on the circle and the parameter β is in the "high temperature" regime β < √ 2. The welding problem is solved by studying a non-uniformly elliptic Beltrami equation with a random complex dilatation. For the existence a method of Lehto is used. This requires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
182
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(186 citation statements)
references
References 34 publications
4
182
0
Order By: Relevance
“…It is natural to conjecture that zipping up gives a welding that respects this measure, and also that SLE 4 is removable. We note that a closely related result has been established by Tecu in [Tec12], which builds on the work of [AJKS11].…”
supporting
confidence: 56%
See 1 more Smart Citation
“…It is natural to conjecture that zipping up gives a welding that respects this measure, and also that SLE 4 is removable. We note that a closely related result has been established by Tecu in [Tec12], which builds on the work of [AJKS11].…”
supporting
confidence: 56%
“…Astala, Jones, Kupiainen, and Saksman showed that the construction Jones proposed produces a well-defined curve [AJKS11,AJKS10], but Binder and Smirnov recently announced a proof (involving multifractal exponents) that this curve is not a form of SLE, and hence the original Jones conjecture is false [Smi] (see Section 1.5). Our construction shows that a simple variant of the Jones conjecture is in fact true.…”
Section: Overviewmentioning
confidence: 99%
“…In the stochastic setting of the Schramm-Loewner evolution SLE κ where the driving term is λ t = √ κB t and B t is a standard one-dimensional Brownian motion, the conformal welding approach leads to interesting and difficult problems, see [36] and [1] for related deep results. In [31], the almost sure continuity of the SLE κ hulls was proved by different means:…”
Section: The Existence Of Loewner Curves When ||λ||mentioning
confidence: 99%
“…They also come into play to construct processes close to curves SLE κ by the conformal welding method [65].…”
Section: E(e Iξρ(b) ) = Exp ψ(ξ)λ(B)mentioning
confidence: 99%